There is unrest in the forest, there is trouble in the trees (extended) - Dagnall, Rebecca (Turner Galleries, 2012)
The images depict the elements of suburban cultural iconography that have become cliché and brings them into an almost uncomfortable realm of high art. The portrait like skulls and creatures that emerge from the landscape itself, echo the haunts of gothic landscape and seduce the audience into a dark and uneasy yet beautifully inviting space. Rebecca Dagnall, 2012